Can Restorative Practices Help to Reduce Disparities in School Discipline Data? A Review of the Literature. (2nd April 2016) - Kline, Dana M. Stewart
Abstract : Disparities in school discipline data is a national concern. Schools across the nation are working to eliminate these disparities. This literature review considers one response to the disproportionate data, restorative practices. This article examines why exclusionary approaches to discipline are ineffective, contribute to imbalanced discipline data, exacerbate the achievement gap, and push minority students into the juvenile justice system. Restorative practices are an inclusionary, nonpunitive alternative. This approach offers a preventive component as well as a responsive component. I will use this article as a platform to show readers how and why using restorative practices, as an alternative to punitive practices, will support a reduction in the number of referrals and suspension given in schools in order to reduce, and ultimately eliminate the disparities in discipline data across the nation. Limitations in the research are highlighted and recommendations of where to focus future research are provided.